TRANSFORMATION OF ISLAMIC EDUCATIONAL ENTREPRENEURSHIP AS A STRATEGY FOR PESANTREN SUSTAINABILITY - Zaki Maulana, Muhammad; Arifin, Misbahul; Abdullah (International Journal of Multidisciplinary Reseach, 2025)
Islamic boarding schools (pesantren) as Islamic educational institutions are facing increasingly complex sustainability challenges due to social change, economic pressures, and the demands of modern educational management. These conditions require pesantren to develop adaptive managerial approaches without losing their Islamic identity and values. This study aims to analyze and construct the concept of transforming Islamic educational entrepreneurship as a strategy for pesantren sustainability. The research focuses on understanding Islamic educational entrepreneurship as an instrument of institutional transformation that integrates shifts in paradigm, values, and pesantren management. This study employs a qualitative approach using library research methods through systematic analysis of international and national scholarly journal articles published since 2020 related to educational entrepreneurship, Islamic entrepreneurship, organizational transformation, and institutional sustainability. The findings indicate that Islamic educational entrepreneurship functions as a catalyst for transforming pesantren management toward financial, institutional, and value-based sustainability. The integration of Islamic values within entrepreneurial practices strengthens social legitimacy and enhances the resilience of pesantren institutions. The implications of this study emphasize the importance of developing a conceptual framework of Islamic educational entrepreneurship as a foundation for formulating sustainable and value-oriented pesantren management strategies.